Life-cycle costing analysis to assist design decisions: beyond 3D building information modelling - Whyte, Andrew; Scott, David (Nottingham University Press, 2010)
Design decisions are increasingly required to take full account of life-cycle-cost to facilitate specification choice for different building and engineering components. To this end an integrated framework for life-cycle analysis through identification of contributory elements and sub-elements allows analysis via an appropriate tool. The framework presented discusses the opportunity for the utilisation of statistics and probability, fuzzy set logic, artificial neural networks and objected orientated analysis to go towards a life-cycle-cost system able to form part of an overarching model supporting decision making within the building design process.